2021
DOI: 10.1155/2021/9498029
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of China’s Lockdown Policy on the Incidence of COVID-19: An Interrupted Time Series Analysis

Abstract: Background. Policy changes are often necessary to contain the detrimental impact of epidemics such as those brought about by coronavirus disease (COVID-19). In the earlier phases of the emergence of COVID-19, China was the first to impose strict restrictions on movement (lockdown) on January 23rd, 2020. A strategy whose effectiveness in curtailing COVID-19 was yet to be determined. We, therefore, sought to study the impact of the lockdown in reducing the incidence of COVID-19. Methods. Daily cases of COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
1
5
0
1
Order By: Relevance
“…It can be reflected that the government's decision to end the lockdown was possibly not appropriate at that time as the lockdown had controlled the COVID-19 transmission and the ending of the lockdown induced its abrupt increase. The findings of this study align with that of India 11 and China 12 both of which found that institutions of lockdown had significantly reduced the daily cases of COVID-19 and contrasts with the case of New Zealand which with early preparation and systematic management managed the COVID-19 cases to keep low without posing a longer lockdown period. 13 The Government of Nepal decided to impose the second lockdown on 29 th April 2021 which ended after four months on the first of September.…”
Section: Discussionsupporting
confidence: 84%
“…It can be reflected that the government's decision to end the lockdown was possibly not appropriate at that time as the lockdown had controlled the COVID-19 transmission and the ending of the lockdown induced its abrupt increase. The findings of this study align with that of India 11 and China 12 both of which found that institutions of lockdown had significantly reduced the daily cases of COVID-19 and contrasts with the case of New Zealand which with early preparation and systematic management managed the COVID-19 cases to keep low without posing a longer lockdown period. 13 The Government of Nepal decided to impose the second lockdown on 29 th April 2021 which ended after four months on the first of September.…”
Section: Discussionsupporting
confidence: 84%
“…However, this must be cautiously inferred as a limited testing and reporting capacity for COVID-19 in Indonesia may have contributed to the lower incidence [ 21 , 22 , 23 ]. Advanced countries such as the USA had more RNA molecular testing facilities, while countries with full lockdowns such as China and New Zealand [ 24 , 25 , 26 , 27 ] showed very low COVID-19 incidence and fatalities [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our trend analysis method is illustrated in Figure 1. In each panel of this figure, we include three separate temporal periods: (1) the period before a public health intervention where data are used to evaluate a possible ''Business-as-Usual (BAU)'' scenario; (2) the period after an intervention, but before it has an impact on public health performance, or a lag in impacts (e.g., see Caristia et al, 2020;Fang et al, 2020;Ghosal et al, 2020;Guzzetta et al, 2021;Molefi et al, 2021;Siedner et al, 2020), what we refer to as a ''Yet-to-be-Impact'' period; and (3) the period after the intervention that coincides with when there is an impact on public health performance, what we refer to as an ''Observed Impact'' period.…”
Section: Methodsmentioning
confidence: 99%